Kuala Kangsar win is people's win, says new MP - New Sabah Times English, (KK) (New Sabah Times, 2016)
KUALA KANGSAR: Barisan Nasional's victory in the Kuala Kangsar parliamentary by election is a manifestation of the constituents' wish for continuity of its development agenda.